Model Pembelajaran Yang Berorientasi Pada Siswa (Pada Konsep Terapung, Tenggelam dan Melayang) - Syahrial Ayub; Agus Ramdani; Ni Nyoman Sri Putu Verawati; Muh. Zuhdi (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: Teaching is a teacher’s daily job. Nevertheless, it turns out that teaching students about how they should study is not easy. This research is included as Research and Development—also known as RnD—which aims to give an actual example of how to teach and to floating and drowned concept in a simple way through Curriculum 2013. The result of the research, which is a student-oriented learning design and learning structure which in turn is an implementation of scientific approach, is the output resulted from a long term study, development and experience obtained by the writer team through teaching and training a number of supervisors, school principals, and teachers in various areas of Indonesia. The responses for this teaching model obtained from the teachers have been very positive, whereby 95% of teachers claimed that they are very interested in the design, and only 5% claimed that they are mildly interested. This thus indicates that this teaching model can become a model to be referred to in teaching using a scientific approach in Curriculum 2013. Keywords: Student Oriented Model, Floating and Drowned